A lithium metal interface protection method and applications thereof
Patent Information
- Application Number
- CN202310040546.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-12
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-01-12
AI Technical Summary
[0003]尽管如此,锂金属电池在商业化的推广和应用中依然受制于其循环效率较低、安全性不良等问题
[0028](1)本发明方法制备得到的界面保护层为锂合金层与聚合物层形成的一体化复合结构;其中,锂合金层与金属锂直接接触,具有高锂离子扩散率;聚合物层在锂合金层外侧;锂合金层可诱导充放电过程中金属锂的均匀沉积;聚合物层保持有孔洞结构为锂离子扩散提供通道并为锂金属沉积提供额外的空间,同时减少了电解液的过度消耗;另外,LiF等无机组分的形成也提高界面保护层的致密度和离子电导率。
Smart Images

Figure CN116504927B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium battery technology, specifically to a method for protecting lithium metal interfaces and its application. Background Technology
[0002] In recent years, the application scenarios for rechargeable lithium-ion batteries have become increasingly widespread, expanding from small electronic devices such as mobile phones and communication equipment to electric vehicles and flexible smart devices. The continuously growing market demand has driven lithium battery research towards higher energy density and improved safety performance, while traditional lithium-ion batteries are far from meeting the needs of the expanding market. With the energy density of existing ternary cathode material systems nearing its limit, researchers have begun to focus on lithium battery anode materials, hoping to develop materials with greater capacity than traditional graphite anodes to improve the energy density of lithium batteries. Lithium metal, due to its extremely low density (0.534 g / cm³),... -3 ), with an extremely high theoretical capacity (3861mAh g). -1 Its extremely low electrochemical potential (-3.04V vs. standard hydrogen electrode (SHE)) makes it the best choice for the next generation of high-energy-density secondary battery anode materials.
[0003] Despite this, the commercialization and application of lithium metal batteries are still constrained by issues such as low cycle efficiency and poor safety. The unique dissolution-deposition mechanism and highly reactive chemical properties of lithium metal mean that lithium metal anodes frequently experience lithium dendrite growth, SEI film rupture, and unlimited volume expansion during repeated charge-discharge cycles. These problems lead to rapid performance degradation in lithium metal batteries and can even cause serious safety issues. Therefore, solving the deposition control problem of lithium metal anodes is crucial for the commercial application of lithium metal batteries.
[0004] Chinese patent document CN112625592A discloses a method for preparing a lithium metal interface modification layer. The invention utilizes a siloxane polymer and a catalyst to mix with a solvent containing lithium salt, stir to obtain a mixture, coat the mixture onto a lithium foil, and heat treat to obtain a lithium metal interface modification layer. The siloxane polymer can weaken the reaction between the solid electrolyte and lithium metal. The polymer cross-links and polymerizes under the action of the catalyst to form a network structure, which can suppress the expansion of lithium metal.
[0005] Chinese patent document CN110212166A discloses a method for constructing a double-layer protective interface on the surface of a lithium metal anode, comprising: (a) esterifying polyphosphoric acid with a polyol to form a polyphosphoric acid ester; (b) adding the polyphosphoric acid ester to an organic solvent to prepare an ester treatment solution; and (c) immersing a lithium metal sheet in the ester treatment solution for an etching reaction. This invention improves the air stability of a metal by forming an organic / inorganic double-layer interface protective layer through in-situ etching on the metal surface, thereby significantly improving its cycle performance and safety performance when used in lithium metal batteries. Summary of the Invention
[0006] This invention provides a method for protecting the lithium metal interface. The method is simple and easy to implement. The resulting interface protection layer is an integrated composite structure formed by a lithium alloy layer and a polymer layer. The lithium alloy layer is in direct contact with the lithium metal, and the lithium alloy layer can induce uniform deposition of lithium metal during charging and discharging. The polymer layer maintains a porous structure to provide channels for lithium-ion diffusion and additional space for lithium metal deposition. The lithium metal anode with an interface protection layer prepared by the method of this invention exhibits excellent cycle stability in liquid batteries.
[0007] The specific technical solution adopted is as follows:
[0008] A method for protecting lithium metal interfaces includes the following steps:
[0009] (1) A precursor treatment liquid is prepared using metal fluorides, lithium salts, polymers and organic solvents as raw materials; wherein the polymer is at least one of polyethylene oxide, polyvinylidene fluoride or poly(vinylidene fluoride-co-hexafluoropropylene);
[0010] (2) The precursor treatment solution is coated onto the surface of the lithium metal electrode and then heat-treated to obtain a lithium metal anode with an interface protection layer.
[0011] This invention modifies the interface of lithium metal electrodes using a precursor treatment solution composed of metal fluoride, lithium salt, polymer and organic solvent. The metal fluoride can react with lithium metal to form a lithium alloy layer and inorganic components such as LiF. Further polymer cross-linking polymerization yields a porous polymer layer, forming a bilayer composite structure of lithium alloy layer and polymer layer.
[0012] In step (1), the metal fluoride is at least one of antimony fluoride, copper fluoride, aluminum fluoride, tin fluoride, tantalum fluoride, and niobium fluoride. The above metal fluorides can react with lithium metal to form a lithium alloy layer and inorganic components such as LiF. The lithium alloy layer can greatly improve the diffusion rate of lithium ions and induce uniform deposition of lithium metal during charging and discharging. Inorganic components such as LiF can improve ionic conductivity and inhibit the growth of lithium dendrites.
[0013] Preferably, the metal fluoride is antimony fluoride, which can react with lithium metal to form a lithium-antimony alloy layer and the inorganic component LiF.
[0014] In step (1), the lithium salt is at least one of lithium nitrate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, and lithium tetrafluoroborate. The addition of the lithium salt can improve the lithium ion transport efficiency of the polymer layer and increase its ionic conductivity.
[0015] Preferably, in step (1), the organic solvent is at least one of ethylene glycol dimethyl ether, tetrahydrofuran, and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, and the above organic solvent can achieve uniform dispersion of each component in the solution.
[0016] Preferably, the concentration of metal fluoride in the precursor treatment solution is 0.05–0.2 mol / L, and the mass fraction of lithium salt is 1–6 wt% and the mass fraction of polymer is 0.2–5 wt% based on the mass of organic solvent.
[0017] More preferably, the concentration of metal fluoride in the precursor treatment solution is 0.075–0.15 mol / L, and the mass fraction of lithium salt is 2–5 wt% and the mass fraction of polymer is 0.4–3 wt% based on the mass of organic solvent.
[0018] Preferably, a uniform precursor treatment solution is prepared by mixing a metal fluoride, a lithium salt, a polymer, and an organic solvent, and then stirring at 40-60°C for 6-15 hours to promote polymer dissolution.
[0019] Further preferred stirring conditions are: 60°C, 12 hours.
[0020] Preferably, the precursor treatment solution is drop-coated onto the surface of the lithium metal anode at a drop volume of 20–40 μL / cm. 2 The drop-coating method for film formation is relatively simple.
[0021] A further preferred method is to apply the coating at a rate of 25 μL / cm. 2 .
[0022] In step (2), heat treatment evaporates the solvent and accelerates polymer film formation. Preferably, the heat treatment conditions are 40-60°C for 60-180 min.
[0023] The present invention also provides a lithium metal battery, including the aforementioned lithium metal anode with an interface protection layer, specifically including a positive electrode, a lithium metal anode with an interface protection layer, a separator, and an electrolyte.
[0024] Preferably, the cathode material is LiFePO4, LiCoO2, or LiNi. 0.8Co 0.1 Mn 0.1 O2, LiNi 0.6 Co 0.2 Mn 0.2 Any of the following: O2.
[0025] Preferably, the diaphragm is selected from the Celgard series of diaphragms.
[0026] Preferably, the electrolyte is an ether-based electrolyte or a carbonate-based electrolyte.
[0027] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0028] (1) The interface protective layer prepared by the method of the present invention is an integrated composite structure formed by a lithium alloy layer and a polymer layer; wherein, the lithium alloy layer is in direct contact with metallic lithium and has a high lithium ion diffusion rate; the polymer layer is on the outside of the lithium alloy layer; the lithium alloy layer can induce uniform deposition of metallic lithium during charging and discharging; the polymer layer maintains a porous structure to provide channels for lithium ion diffusion and additional space for lithium metal deposition, while reducing excessive consumption of electrolyte; in addition, the formation of inorganic components such as LiF also improves the density and ionic conductivity of the interface protective layer.
[0029] (2) The lithium metal electrode modified with the interface protective layer can realize rapid material exchange on the electrode surface, which significantly reduces battery polarization. The interface protective layer can adapt to changes in electrode volume and induce uniform deposition of lithium metal. Applying the lithium metal anode with the interface protective layer prepared in this invention to liquid batteries can effectively extend the cycle life of the battery. Attached Figure Description
[0030] Figure 1 The graph shows the cycle efficiency of the lithium metal battery assembled in Comparative Example 1.
[0031] Figure 2 The graph shows the cycle efficiency of the lithium metal battery assembled in Example 1.
[0032] Figure 3 This is a SEM image of the lithium metal anode with an interface protective layer in Example 2.
[0033] Figure 4 The graph shows the cycle efficiency of the lithium metal battery assembled in Example 2.
[0034] Figure 5 This is a SEM image of the lithium metal anode with an interface protective layer in Example 3.
[0035] Figure 6 This is a cross-sectional SEM image of the lithium metal anode with an interface protective layer in Example 3.
[0036] Figure 7 The graph shows the cycle efficiency of the lithium metal battery assembled in Example 3. Detailed Implementation
[0037] The present invention will be further illustrated below with reference to the embodiments and accompanying drawings. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention.
[0038] Comparative Example 1
[0039] Untreated lithium metal sheets were assembled with LiFePO4 cathode sheets, Celgard 2320 separators, and ether electrolytes to form a lithium metal battery. The battery was first cycled 5 times at 0.1C, then subjected to a longer cycle at 0.5C. After 70 cycles, the capacity retention was 77.92%; the cycle efficiency is shown in the figure below. Figure 1 As shown.
[0040] Example 1
[0041] Antimony fluoride (SbF3) was dissolved in ethylene glycol dimethyl ether to prepare a solution with a concentration of 0.05 mol / L. Then, 1 wt% lithium nitrate, 2 wt% lithium bis(trifluoromethanesulfonyl)imide, 0.8 wt% polyethylene oxide and 1.2 wt% poly(vinylidene fluoride-co-hexafluoropropylene) were added by mass fraction of the solvent. The mixture was stirred at 60°C for 12 hours to obtain the precursor treatment solution.
[0042] The precursor treatment solution was uniformly dispersed on the lithium metal electrode using a drop-coating method, with a drop-coating amount of 20 μL / cm². 2 After the solvent evaporates, the metal lithium anode is dried in a vacuum oven at 60°C for 120 minutes to obtain a metal lithium anode with an interface protective layer.
[0043] A lithium metal anode with an interface protection layer was assembled with a LiFePO4 cathode, a Celgard 2320 separator, and an ether electrolyte to form a lithium metal battery. The battery was first cycled 5 times at 0.1C, followed by a longer cycle at 0.5C. After 160 cycles, the capacity retention was 84.14%. The cycle efficiency is shown in the figure below. Figure 2 As shown.
[0044] Example 2
[0045] The lithium metal interface protection method in this embodiment differs from that in Example 1 only in that the concentration of antimony fluoride (SbF3) is 0.1 mol / L and the mass fraction of lithium nitrate is 2 wt%; thus, a lithium metal anode with an interface protection layer is obtained.
[0046] The SEM image of the lithium metal anode with an interface protective layer is shown below. Figure 3As shown, the modified lithium metal electrode surface polymers are interconnected to form a honeycomb-like structure with a relatively flat surface. The pores are nearly circular in shape and uniform in size. The bottom lithium antimony alloy is covered by the polymer layer.
[0047] A lithium metal battery was assembled by combining a lithium metal anode with an interface protection layer, a lithium iron phosphate cathode, a Celgard 2320 separator, and an ether electrolyte. The battery was first cycled 5 times at 0.1C, followed by a longer cycle at 0.5C. After 400 cycles, the capacity retention was 88.88%. The cycle efficiency is shown in the figure below. Figure 4 As shown.
[0048] Example 3
[0049] The lithium metal interface protection method in this embodiment differs from the method in Example 2 only in that the mass fraction of polyethylene oxide is 0.2 wt% and the mass fraction of poly(vinylidene fluoride-co-hexafluoropropylene) is 0.3 wt%; thus, a lithium metal anode with an interface protection layer is obtained.
[0050] The SEM image of the lithium metal anode with an interface protective layer is shown below. Figure 5 As shown, the lithium-antimony alloy particles at the bottom of the modified lithium metal electrode are cross-linked together by polymers, forming a multi-layered mesh-like structure. The pore diameters are all approximately the same and the distribution is relatively uniform. Cross-sectional SEM images are shown below. Figure 6 As shown, the structure of the interface layer can be clearly observed on the lithium metal substrate, with a lithium-antimony alloy layer at the bottom and a polymer layer at the top.
[0051] A lithium metal anode with an interface protection layer was assembled with a lithium iron phosphate cathode, a Celgard 2320 separator, and an ether electrolyte to form a lithium metal battery. The battery was first cycled 5 times at 0.1C, then subjected to a longer cycle at 0.5C. After 560 cycles, the capacity retention was 94.6%. The cycle efficiency is shown in the figure below. Figure 7 As shown.
[0052] Example 4
[0053] The only difference between the lithium metal interface protection method in this embodiment and the method in Embodiment 3 is that aluminum fluoride is used as the metal fluoride; thus, a lithium metal anode with a protective layer is obtained.
[0054] Example 5
[0055] The only difference between the lithium metal interface protection method in this embodiment and the method in Embodiment 3 is that copper fluoride is used as the metal fluoride; thus, a lithium metal anode with a protective layer is obtained.
[0056] Example 6
[0057] The lithium metal interface protection method in this embodiment differs from the method in Example 3 only in that the polymer content ratio is 0.8 wt% polyethylene oxide and 1.2 wt% polyvinylidene fluoride; thus, a lithium metal anode with a protective layer is obtained.
[0058] Example 7
[0059] The lithium metal interface protection method in this embodiment differs from that in Example 3 only in that the polymer content ratio is 2wt% polyvinylidene fluoride; thus, a lithium metal anode with a protective layer is obtained.
[0060] Example 8
[0061] The lithium metal interface protection method in this embodiment differs from the method in Example 3 only in that the solvent is tetrahydrofuran; a lithium metal anode with an interface protection layer is obtained.
[0062] Example 9
[0063] The lithium metal interface protection method in this embodiment differs from the method in Example 3 only in that the solvent is 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether; thus, a lithium metal anode with an interface protection layer is obtained.
[0064] Example 10
[0065] The lithium metal interface protection method in this embodiment differs from the method in Example 3 only in that the lithium salt content ratio is 2wt% lithium di(trifluoromethanesulfonyl)imide and 2wt% lithium tetrafluoroborate; thus, a lithium metal anode with an interface protection layer is obtained.
[0066] Example 11
[0067] The lithium metal interface protection method in this embodiment differs from that in Example 3 only in that the dropping amount of the precursor treatment solution is 30 μL / cm. 2 A lithium metal anode with an interface protective layer was obtained.
[0068] Example 12
[0069] The lithium metal interface protection method in this embodiment differs from that in Example 3 only in that the dropping amount of the precursor treatment solution is 40 μL / cm. 2 A lithium metal anode with an interface protective layer was obtained.
[0070] The embodiments described above provide a detailed explanation of the technical solutions of the present invention. It should be understood that the above descriptions are merely specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, additions, or similar substitutions made within the scope of the principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A lithium metal battery, characterized in that, It includes a positive electrode, a lithium metal negative electrode with an interface protective layer, a separator, and an electrolyte. The positive electrode material is selected from LiFePO4, LiCoO2, and LiNi. 0.8 Co 0.1 Mn 0.1 O2, LiNi 0.6 Co 0.2 Mn 0.2 Any one of O2, the diaphragm is selected from the Celgard series diaphragm, and the electrolyte is an ether electrolyte or a carbonate electrolyte; The preparation method of a lithium metal anode with an interface protective layer includes the following steps: (1) A precursor treatment liquid is prepared using metal fluorides, lithium salts, polymers and organic solvents as raw materials; the polymers are polyethylene oxide and poly(vinylidene fluoride-co-hexafluoropropylene); (2) The precursor treatment solution is coated onto the surface of the lithium metal electrode, and after heat treatment at 40~60 ℃ for 60~180 min, a lithium metal anode with an interface protective layer is obtained. The metal fluoride is antimony fluoride; The lithium salts are lithium nitrate and lithium bis(trifluoromethanesulfonyl)imide; The organic solvent is ethylene glycol dimethyl ether; The concentration of metal fluoride in the precursor treatment solution is 0.05~0.2 mol / L, and the mass fraction of lithium salt is 1~6 wt% and the mass fraction of polymer is 0.2~5 wt% based on the mass of organic solvent.
2. The lithium metal battery according to claim 1, characterized in that, The precursor treatment solution is prepared by mixing metal fluoride, lithium salt, polymer, and organic solvent and stirring at 40-60 °C for 6-15 hours.
3. The lithium metal battery according to claim 1, characterized in that, The precursor treatment solution was drop-coated onto the surface of the lithium metal anode at a rate of 20–40 μL / cm². 2 .
Citation Information
Patent Citations
Method for constructing double-layer protective interface on surface of lithium metal negative electrode
CN110212166A
Preparation method of lithium metal interface modification layer
CN112625592A
Preparation method of lithium metal negative electrode and lithium metal negative electrode
CN113299886A
Bifunctional interface modification layer for solid-state lithium battery and lithium battery
CN115064779A